KHAZANAH ULAMA HADIS NUSANTARA: MANHAJ DZAWI AN-NADHAR KARYA EMAS MAHFUDZ TERMAS - Tsalis Muttaqin (UIN Raden Mas Said Surakarta, 2015)
Manhaj Dzawi An-Nadhar is as one of the best literature inthe filed of Hadis which is writtten by an Indonesian Ulama,Muhammad Mahfudh bin Abdullah At-Tirmasiy. It has well known asa masterwork which is scientifically qualified and acknowledge bemutual accroding to the Islamic tecahing tradition compared to thegolden age. This masterwork has been used as one of the primaryreferences in Al-Azhar University‟s libarary, Cairo. Eventhough, whathas been trying by Hadratus Syaikh Hasyim Asy‟ari to socializing hadisand ulumul hadis in Indonesia, seemed broken off and stopped away.Trend of the Indonesian Islamic studies has been always absorbed andmore focusing on the tasawuf and fiqih.